THE INFLUENCE OF INTERNAL CONTROL ON THE POSITIVE QUALITY ON THE POSITIVE IMAGE OF REGIONAL PUBLIC DRINKING WATER COMPANY (PERUMDA) TIRTA JENEBERANG IN GOWA REGENCY. - Fitriani, Fitriani; Sitti Nurbaya; Dg. Maklassa (International Journal of Economic Research and Financial Accounting, 2024)
This research is a quantitative study aimed at determining the influence of internal control and service quality on the positive image of the regional public drinking water company Tirta Jeneberang in Gowa Regency. The sample was taken from the PERUMDA Office in Gowa Regency. The type of data used in this research is quantitative data obtained from questionnaires distributed and related to the researched problem. Data collection was conducted through observation and questionnaire distribution. In this study, the data sources used in data collection included primary data and secondary data. The research instrument used in this study employed the Likert scale method. The research results show that through statistical calculations using the Statistical Package for the Social Science (SPSS) version 27 regarding the influence of internal control and service quality on the positive image of PDAM customers, as discussed in the previous chapters, the author draws the important conclusion that internal control and service quality have a positive and significant influence on the positive image of the company. Internal control and service quality must be maintained and improved because it can be seen from the research results that the existing internal control and service quality are already sufficiently stable and efficient in providing a positive image for the company.